Isolation of Secondary Metabolite A. niger âIn-Habitingâ Queen M. gilvus Hagen.âs Nest - Alen, Yohannes; Melati, Atika; Sarina, Gemmy; Djamaan, Akmal (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Aspergillus niger is pathogen fungi that can live in various locations and can live contiguous with many hosts, one of them is queen termiteâs nest. The aims of the study were to isolated the secondary metabilite of A.niger. Extraction proccess of secondary metabolite compounds was carried out by maceration method using methanol solvent. Based on that proccess, methanol extract was be yield 4,32% sample weight. Fractination proccess was carried out in the separating funnel using ethyl acetate solvent, which ethyl acetate fraction was be yield 14.39% methanol extract. Separation of the compounds was carried out by column chromatography method using n-hexane and ethyl asetate eluents. Purification of the compounds were done by recrystallization method using n-hexane and ethyl asetate. Two secondary metabolite compounds were successfully isolated from ethyl acetate fraction of the methanolic extract of fungus A. niger âIn-Habitingâ queen termiteâs nest M. gilvus Hagen. Based on organoleptic examination, the compound signed AM-12-22-01 is 35 mg, white needle crystals, melting point 151-153 oC. While, the AM-12-60-01* is 15 mg, white needle crystals, melting point 91-93 oC. Based on the chemical analysis, thin layer chromatography, ultraviolet and infrared spectra data it was identified that AM-12-22-01 and AM-12-60-01 were a phenolic compounds.Key words: isolation, A. niger, In-Habiting, M. gilvus Hagen.